Accessing MHz Operation at 2 V with Field‐Effect Transistors Based on Printed Polymers on Plastic. Issue 4 (14th December 2018) - Perinot, Andrea; Caironi, Mario
Abstract: Organic printed electronics are suitable for the development of wearable, lightweight, distributed applications in combination with cost‐effective production processes. Nonetheless, some necessary features for several envisioned disruptive mass‐produced products are still lacking: among these radio‐frequency (RF) communication capability, which requires high operational speed combined with low supply voltage in electronic devices processed on cheap plastic foils. Here, it is demonstrated that high‐frequency, low‐voltage, polymer field‐effect transistors can be fabricated on plastic with the sole use of a combination of scalable printing and digital laser‐based techniques. These devices reach an operational frequency in excess of 1 MHz at the challengingly low bias voltage of 2 V, and exceed 14 MHz operation at 7 V. In addition, when integrated into a rectifying circuit, they can provide a DC voltage at an input frequency of 13.56 MHz, opening the way for the implementation of RF devices and tags with cost‐effective production processes. Abstract : High‐frequency, low‐voltage polymer field‐effect transistors, fabricated on plastic with the sole use of scalable techniques, enable a feasible route toward low‐cost, mass‐scale production of organic devices for radio frequency applications. High operational frequency in excess of 1 MHz at challengingly low bias voltage of 2 V and a rectifier circuit operating at an input frequency of 13.56 MHz are demonstrated.